Total Synthesis of a Pyrrole Lactone Alkaloid, Longanlactone. Issue 28 (15th August 2014) - Reddy, Chada Raji; Reddy, Motatipally Damoder; Dilipkumar, Uredi
Abstract: The first asymmetric total synthesis of the natural pyrrole lactone longanlactone has been achieved. The key reactions, a Barbier propargylation and a Paal–Knorr pyrrole synthesis, have provided easy access to the target natural product fromL ‐aspartic acid in six steps and 31 % overall yield. The C‐4 epimer of the natural product and propionyllonganlactone have also been prepared by this strategy. Abstract : The first total synthesis of a new pyrrole lactone alkaloid, longanlactone, along with its C‐4 epimer is achieved from the natural amino acidL ‐aspartic acid with a Barbier‐type propargylation and a Paal–Knorr pyrrole synthesis as key steps.